MicroRNA roles and their potential use as selection tool to cold tolerance of domesticated teleostean species: A systematic review - Blödorn, Eduardo B.; Domingues, William B.; Nunes, Leandro S.; Komninou, Eliza R.; Pinhal, Danillo [UNESP]; Campos, Vinicius F. (Elsevier, 2021)
Thermal tolerance is a highly valuable trait for aquaculture. However, complex regulatory mechanisms prevent conventional molecular markers, based on DNA, from being effective. Thus, in order to search for potential cold-tolerance biomarkers in fish at a post-transcriptional level, the aim of this work is to systematic review current literature on miRNAs related to low temperature in teleost fish and answer the question: are there any miRNAs related to key mechanisms of cold-tolerance in fish? Through a systematic search in 3 different databases, a total of 418 studies were initially identified. After criterious screening, 6 studies were included in the systematic review. At least 71 miRNAs were reported to be differentially expressed (DE) in fish exposed to low temperatures, from which 29 were considered up regulated and 42 down regulated in cold stressed fish. Among the total number of DE miRNAs, 6 were found to be present in at least two studies: miR-9-3p, miR-135c, miR-9-5p, miR-30b, miR-122, miR-92a-3p. DE miRNAs presented in at least two studies were submitted to DIANA mirPath v.3 to identify potential target genes using microT-CDS v 5.0 database. These miRNAs potentially target key regulatory enzymes to glucose and lipid metabolism, controlling the shift in energy metabolism required for cold adaptation. FoxO signaling and circadian cycle are also very likely involved in thermal tolerance mechanisms. These findings represent potential targets for further investigation of microRNA-based predictive tools for fish cold tolerance.
Keywords: Acclimation; Biomarker; Cold stress; Epigenetic marker; Low temperature; miRNA